Identification of Islamic environmental principles in the courtyard special arrangement: a case study of USIM - Mohamad Azmi, Nor Farhana; Harun, Nor Zalina (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
This paper is about identification of Islamic environmental principles in courtyard spatial arrangement in the campus of Islamic Science University of Malaysia(USIM).This paper is aimed to recommend Islamic design guidelines for a courtyard spatial arrangement to create a conducive outdoor learning environment in the campus area. In order to achieve the aim of the study, there are three objectives there are three objectives identified which are; to study the characteristics of a good courtyard for outdoor learning, to identify activities conducted in a courtyard and to examine the existing courtyard in the study area for optimum utilization. This research used the methodology of study which consists of observation, questionnaire survey and site mapping that is being conducted in three selected areas which are Faculty of Quranic and Sunnah Studies, Faculty of Leadership and Management and Faculty of Syariah and Law. 30-50 respondents were chosen to answer the questionnaire and to know their comments on the existing courtyard.The findings concluded that three of the courtyard should be redesigned to improve the courtyard area for an outdoor learning environment.Thus, the results suggested that an Islamic courtyard could be applied into the design of courtyard spatial arrangement.